Effect of Melaleuca leucadendron, Cananga odorata and Pogostemon cablin Oil Odors on Human Physiological Responses - Rini Pujiarti; Yoshito Ohtani; Titis Budi Widowati; Wahyudi Wahyudi; Kasmudjo Kasmudjo; N. Kaushalya Herath; Chao Nan Wang (Masyarakat Peneliti Kayu Indonesia, 2012)
The aims of this study were to evaluate the main compounds and the effect of M. leucadendron, C. odorata and P. cablin essential oil odors on human physiological responses. The chemical compounds of essential oils in this study were analyzed by gas chromatography-mass spectrometry (GC-MS) and the physiological effects of essential oils on human were analyzed via the sense of smell olfactory system. Physiological parameters of systolic blood pressure, diastolic blood pressure, pulse rate, stress index, and brain wave were recorded before and after sniffing essential oils. The result shows that the main compound of M. leucadendron, C. odorata, and P. cablin is 1,8-cineole, Caryophyllene and Patchouli Alcohol, respectively. Our results demonstrated that M. leucadendron and C. odorata oil odors possessed sedative effect and P. cablin oil odor had tendency to contain stimulating effect on human physiologies.